The impact of corporate social responsibility on the financial performance of Georgian banks - Kasradze, Tea; Machkhashvili, Sopio (Journal of Eastern European and Central Asian Research (JEECAR), 2024)
Corporate social responsibility (CSR) is a topical issue of global importance, which is due, on the one hand, to the United Nations Sustainable Development Agenda and, on the other hand, to business awareness of it as a strategic tool. In Georgia, an activation of financial institutions in the direction of CSR has been observed in recent years. The presented paper aims to study the impact of actions taken by banks within the framework of corporate social responsibility on financial performance. The research is developed using deductive reasoning and statistical research methods, and the hypothesis is tested through correlation regression analysis. Secondary data is used in the study. The values of the correlation coefficient confirmed that the performance of CSR by the banks has a positive impact on their financial ratios: return on equity (ROE) and return on assets (ROA).